2005
DOI: 10.1159/000086401
|View full text |Cite
|
Sign up to set email alerts
|

Use of Illegally Acquired Medical Opioids by Opiate-Dependent Patients in Detoxification Treatment

Abstract: Take-home dosages in maintenance treatment are of great therapeutic importance, but they include the risk of the substitute being distributed illegally. We reviewed the extent of consumption of illegally acquired medical opiates by 142 opiate- or poly-addicted patients consecutively admitted to a detoxification ward. 76 (53.5%) of them admitted to taking illegally acquired medical opiates, usually methadone, at least once. The cumulative duration was 30 days (median). Motivation was usually due to difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
3
11
0
2
Order By: Relevance
“…Along with previous findings (Scherbaum et al, 2005), financial aspects seemed to be important, at least among participants currently not in OST. Among OST patients, insufficient dosage and problems to comply with treatment regulations were the main reasons for NPU, which may point to a mismatch between patient expectations and the mode of OST delivery (Schulte, Gansefort, Stöver, & Reimer, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Along with previous findings (Scherbaum et al, 2005), financial aspects seemed to be important, at least among participants currently not in OST. Among OST patients, insufficient dosage and problems to comply with treatment regulations were the main reasons for NPU, which may point to a mismatch between patient expectations and the mode of OST delivery (Schulte, Gansefort, Stöver, & Reimer, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…the lower prices of substitution medication compared to heroin (EMCDDA, 2005;Scherbaum, Kluwig, Meiering, & Gastpar, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors stated that both drugs have high rates of misuse, including doctor shopping, i.e. seeing multiple treatment providers to procure prescription medications illicitly; illicit intravenous application; snorting; and buying or selling on the black market [107][108][109][110].…”
Section: European Studiesmentioning
confidence: 99%
“…German data from patients admitted for detoxification showed that 53.5% misused medical opioids, especially methadone [110], mainly because of difficulty in acquiring heroin.…”
Section: European Studiesmentioning
confidence: 99%